Analysis of E-Commerce Usage for Micro, Small, and Medium Enterprises (MSMEs) - Jennatul Ma’wa; Hafidz Ubaidillah; Abu Lukman; Mashudi (Penerbit Hellow Pustaka, 2025)
The development of information technology has brought significant changes across various sectors, including Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. One of the key innovations driving this transformation is e-commerce, which enables MSMEs to expand their market reach and improve operational efficiency. This article aims to explore the impact of e-commerce adoption on MSMEs in Indonesia through a qualitative approach based on the latest literature review. The analysis results indicate that the use of e-commerce provides various benefits, such as increased market access, reduced operational costs, and higher revenue for MSMEs. However, there are several challenges that still persist, including low digital literacy, limited infrastructure, and data security issues. Therefore, synergy between the government, industry players, and educational institutions is required to enhance the digital capabilities of MSMEs, ensuring that the potential of e-commerce can be optimally utilized.